The effects of wartime institutions on households' ability to cope with shocks: Evidence for Colombia - Ana María Ibá\~nez; Julián Arteaga; Juan Camilo Cárdenas Campo; Ana Arjona; Patricia Justino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper studies the legacies of wartime institutions, measured as rebelocracy, on the ability of households to cope with negative income shocks. Rebelocracy is the social order established by non-state armed actors in the communities they control. By providing public goods and a predictable framework within which to operate, rebelocracy may generate incentives for households to expand production and accumulate wealth, placing them in a higher income trajectory than households living in war zones amid violence and chaos. If these better economic conditions persist after non-state armed actors leave the territory, households in communities that had stronger rebelocracy levels will be better able to cope with negative income shocks. The empirical strategy identifies households' responses to random weather shocks and estimates their heterogeneous impact by the level of rebelocracy. Using a household panel in four conflict regions in Colombia, the estimation controls for time-invariant unobservables. The study finds that in regions with strong rebelocracy, households are better able to cope with negative weather shocks than those living in regions with non-state armed actor presence but with limited or no intervention. The former households face a lower economic impact of weather shocks and resort less to survival migration. The effect of rebelocracy is driven mostly by the provision of public goods by non-state armed actors. While this paper is not claiming causal impacts of rebelocracy, its coefficient estimates are robust to controlling for confounders that may explain rebelocracy in the first place.
Keywords: D74; H56; O54; Q54; R23; 330; armed conflict; Colombia; institutions; migration; weather shocks